2018
DOI: 10.1590/0101-60830000000153
|View full text |Cite
|
Sign up to set email alerts
|

Lithium interactions with non-steroidal anti-inflammatory drugs and diuretics – A review

Abstract: Background: Lithium is often used in bipolar disorder and occasionally in unipolar depression. Non-steroidal anti-inflammatory drugs (NSAIDs) and diuretics are frequently prescribed and their interaction with lithium is based mainly in few small studies. Objectives: Conduct a review, identify different interaction patterns and discuss treatment options. Methods: Three searches were made in PubMed in January 2016: 1) using the keywords "lithium" [and] "non-steroidal anti-inflammatory"; 2) using the keywords "l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Moreover, men showed lower aLi compared to women, possibly due to a larger lean mass and less fat mass compared to women [27]. Diuretics, ACE inhibitors, AT1 antagonists, and NSAIDs have previously been associated with lithium intoxication or increased lithium concentration [18,[28][29][30][31][32][33]. Likewise, it has been reported that the creatinine clearance gradually decreased in patients when combining these target drugs [19,20,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, men showed lower aLi compared to women, possibly due to a larger lean mass and less fat mass compared to women [27]. Diuretics, ACE inhibitors, AT1 antagonists, and NSAIDs have previously been associated with lithium intoxication or increased lithium concentration [18,[28][29][30][31][32][33]. Likewise, it has been reported that the creatinine clearance gradually decreased in patients when combining these target drugs [19,20,34].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, only NSAIDs showed a positive association with aLi independent from other factors. NSAIDs reduce lithium clearance by inhibition of renal prostaglandin synthesis [14], leading to 2 processes that can increase aLi simultaneously: (I) decreased renal blood flow and (II) increased tubular sodium and lithium reabsorption [14,18,40]. Thus, the 2-sided attack may explain the significant association of NSAIDs independent from other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether a substance was considered psychiatric or somatic co-medication was dependent on the respective indication/diagnosis. Risk medication, that is medication which increases the risk for lithium intoxication, includes thiazide (Ward, Musa et al 1994, Finley, Warner et al 1995, Berkowitz 2001) and loop diuretics (Okusa and Crystal 1994, Finley, Warner et al 1995, Oakley, Whyte et al 2001, Nunes 2018, ACE inhibitors (Finley, Warner et al 1995, Finley, O'Brien et al 1996, Nunes 2018, ARBs (Su, Chang et al 2007, Hayashi, Nishida et al 2016, Nagamine 2020, and NSAIDs (Okusa and Crystal 1994, Ward, Musa et al 1994, Oakley, Whyte et al 2001). While there are limited studies investigating the impact of ARB on lithium clearance, their pharmacodynamic similarity to ACE inhibitors, combined with the well-established link between ACE inhibitors and an increased risk of lithium intoxication (Finley et al, 1995(Finley et al, , 1996Juurlink et al, 2004), led us to include ARB in the risk medication category.…”
Section: Clinical Variablesmentioning
confidence: 99%
“…Some evidence also indicates that NSAIDs can reduce the therapeutic index and precipitate the toxicity of drugs like lithium 3. NSAIDs can also act synergistically to precipitate bleeding with antidepressants4; patients on lithium or antidepressants who are taking or about to start taking NSAIDs must inform their doctors for proper monitoring and dosing.…”
mentioning
confidence: 99%